lean2/library/data/rat/order.lean

445 lines
16 KiB
Text
Raw Normal View History

/-
Copyright (c) 2015 Jeremy Avigad. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Author: Jeremy Avigad
Adds the ordering, and instantiates the rationals as an ordered field.
-/
import data.int algebra.ordered_field algebra.group_power data.rat.basic
open quot eq.ops
/- the ordering on representations -/
namespace prerat
section int_notation
open int
variables {a b : prerat}
definition pos (a : prerat) : Prop := num a > 0
definition nonneg (a : prerat) : Prop := num a ≥ 0
theorem pos_of_int (a : ) : pos (of_int a) ↔ (a > 0) :=
!iff.rfl
theorem nonneg_of_int (a : ) : nonneg (of_int a) ↔ (a ≥ 0) :=
!iff.rfl
theorem pos_eq_pos_of_equiv {a b : prerat} (H1 : a ≡ b) : pos a = pos b :=
propext (iff.intro (num_pos_of_equiv H1) (num_pos_of_equiv H1⁻¹))
theorem nonneg_eq_nonneg_of_equiv (H : a ≡ b) : nonneg a = nonneg b :=
have H1 : (0 = num a) = (0 = num b),
from propext (iff.intro
(assume H2, eq.symm (num_eq_zero_of_equiv H H2⁻¹))
(assume H2, eq.symm (num_eq_zero_of_equiv H⁻¹ H2⁻¹))),
calc
nonneg a = (pos a 0 = num a) : propext !le_iff_lt_or_eq
... = (pos b 0 = num a) : pos_eq_pos_of_equiv H
... = (pos b 0 = num b) : H1
... = nonneg b : propext !le_iff_lt_or_eq
theorem nonneg_zero : nonneg zero := le.refl 0
theorem nonneg_add (H1 : nonneg a) (H2 : nonneg b) : nonneg (add a b) :=
show num a * denom b + num b * denom a ≥ 0,
from add_nonneg
(mul_nonneg H1 (le_of_lt (denom_pos b)))
(mul_nonneg H2 (le_of_lt (denom_pos a)))
theorem nonneg_antisymm (H1 : nonneg a) (H2 : nonneg (neg a)) : a ≡ zero :=
have H3 : num a = 0, from le.antisymm (nonpos_of_neg_nonneg H2) H1,
equiv_zero_of_num_eq_zero H3
theorem nonneg_total (a : prerat) : nonneg a nonneg (neg a) :=
or.elim (le.total 0 (num a))
(suppose 0 ≤ num a, or.inl this)
(suppose 0 ≥ num a, or.inr (neg_nonneg_of_nonpos this))
theorem nonneg_of_pos (H : pos a) : nonneg a := le_of_lt H
theorem ne_zero_of_pos (H : pos a) : ¬ a ≡ zero :=
assume H', ne_of_gt H (num_eq_zero_of_equiv_zero H')
theorem pos_of_nonneg_of_ne_zero (H1 : nonneg a) (H2 : ¬ a ≡ zero) : pos a :=
have num a ≠ 0, from suppose num a = 0, H2 (equiv_zero_of_num_eq_zero this),
lt_of_le_of_ne H1 (ne.symm this)
theorem nonneg_mul (H1 : nonneg a) (H2 : nonneg b) : nonneg (mul a b) :=
mul_nonneg H1 H2
theorem pos_mul (H1 : pos a) (H2 : pos b) : pos (mul a b) :=
mul_pos H1 H2
end int_notation
end prerat
local attribute prerat.setoid [instance]
/- The ordering on the rationals.
The definitions of pos and nonneg are kept private, because they are only meant for internal
use. Users should use a > 0 and a ≥ 0 instead of pos and nonneg.
-/
namespace rat
open nat int
variables {a b c : }
/- transfer properties of pos and nonneg -/
private definition pos (a : ) : Prop :=
quot.lift prerat.pos @prerat.pos_eq_pos_of_equiv a
private definition nonneg (a : ) : Prop :=
quot.lift prerat.nonneg @prerat.nonneg_eq_nonneg_of_equiv a
private theorem pos_of_int (a : ) : (a > 0) ↔ pos (of_int a) :=
prerat.pos_of_int a
private theorem nonneg_of_int (a : ) : (a ≥ 0) ↔ nonneg (of_int a) :=
prerat.nonneg_of_int a
private theorem nonneg_zero : nonneg 0 := prerat.nonneg_zero
private theorem nonneg_add : nonneg a → nonneg b → nonneg (a + b) :=
quot.induction_on₂ a b @prerat.nonneg_add
private theorem nonneg_antisymm : nonneg a → nonneg (-a) → a = 0 :=
quot.induction_on a
(take u, assume H1 H2,
quot.sound (prerat.nonneg_antisymm H1 H2))
private theorem nonneg_total (a : ) : nonneg a nonneg (-a) :=
quot.induction_on a @prerat.nonneg_total
private theorem nonneg_of_pos : pos a → nonneg a :=
quot.induction_on a @prerat.nonneg_of_pos
private theorem ne_zero_of_pos : pos a → a ≠ 0 :=
quot.induction_on a (take u, assume H1 H2, prerat.ne_zero_of_pos H1 (quot.exact H2))
private theorem pos_of_nonneg_of_ne_zero : nonneg a → ¬ a = 0 → pos a :=
quot.induction_on a
(take u,
assume h : nonneg ⟦u⟧,
suppose ⟦u⟧ ≠ (rat.of_num 0),
have ¬ (prerat.equiv u prerat.zero), from assume H, this (quot.sound H),
prerat.pos_of_nonneg_of_ne_zero h this)
private theorem nonneg_mul : nonneg a → nonneg b → nonneg (a * b) :=
quot.induction_on₂ a b @prerat.nonneg_mul
private theorem pos_mul : pos a → pos b → pos (a * b) :=
quot.induction_on₂ a b @prerat.pos_mul
private definition decidable_pos (a : ) : decidable (pos a) :=
quot.rec_on_subsingleton a (take u, int.decidable_lt 0 (prerat.num u))
/- define order in terms of pos and nonneg -/
protected definition lt (a b : ) : Prop := pos (b - a)
protected definition le (a b : ) : Prop := nonneg (b - a)
definition rat_has_lt [reducible] [instance] [priority rat.prio] : has_lt rat :=
has_lt.mk rat.lt
definition rat_has_le [reducible] [instance] [priority rat.prio] : has_le rat :=
has_le.mk rat.le
protected lemma lt_def (a b : ) : (a < b) = pos (b - a) :=
rfl
protected lemma le_def (a b : ) : (a ≤ b) = nonneg (b - a) :=
rfl
theorem of_int_lt_of_int_iff (a b : ) : of_int a < of_int b ↔ a < b :=
iff.symm (calc
a < b ↔ b - a > 0 : iff.symm !sub_pos_iff_lt
... ↔ pos (of_int (b - a)) : iff.symm !pos_of_int
... ↔ pos (of_int b - of_int a) : !of_int_sub ▸ iff.rfl
... ↔ of_int a < of_int b : iff.rfl)
theorem of_int_lt_of_int_of_lt {a b : } (H : a < b) : of_int a < of_int b :=
iff.mpr !of_int_lt_of_int_iff H
theorem lt_of_of_int_lt_of_int {a b : } (H : of_int a < of_int b) : a < b :=
iff.mp !of_int_lt_of_int_iff H
theorem of_int_le_of_int_iff (a b : ) : of_int a ≤ of_int b ↔ (a ≤ b) :=
iff.symm (calc
a ≤ b ↔ b - a ≥ 0 : iff.symm !sub_nonneg_iff_le
... ↔ nonneg (of_int (b - a)) : iff.symm !nonneg_of_int
... ↔ nonneg (of_int b - of_int a) : !of_int_sub ▸ iff.rfl
... ↔ of_int a ≤ of_int b : iff.rfl)
theorem of_int_le_of_int_of_le {a b : } (H : a ≤ b) : of_int a ≤ of_int b :=
iff.mpr !of_int_le_of_int_iff H
theorem le_of_of_int_le_of_int {a b : } (H : of_int a ≤ of_int b) : a ≤ b :=
iff.mp !of_int_le_of_int_iff H
theorem of_nat_lt_of_nat_iff (a b : ) : of_nat a < of_nat b ↔ a < b :=
by rewrite [*of_nat_eq, of_int_lt_of_int_iff, int.of_nat_lt_of_nat_iff]
theorem of_nat_lt_of_nat_of_lt {a b : } (H : a < b) : of_nat a < of_nat b :=
iff.mpr !of_nat_lt_of_nat_iff H
theorem lt_of_of_nat_lt_of_nat {a b : } (H : of_nat a < of_nat b) : a < b :=
iff.mp !of_nat_lt_of_nat_iff H
theorem of_nat_le_of_nat_iff (a b : ) : of_nat a ≤ of_nat b ↔ a ≤ b :=
by rewrite [*of_nat_eq, of_int_le_of_int_iff, int.of_nat_le_of_nat_iff]
theorem of_nat_le_of_nat_of_le {a b : } (H : a ≤ b) : of_nat a ≤ of_nat b :=
iff.mpr !of_nat_le_of_nat_iff H
theorem le_of_of_nat_le_of_nat {a b : } (H : of_nat a ≤ of_nat b) : a ≤ b :=
iff.mp !of_nat_le_of_nat_iff H
theorem of_nat_nonneg (a : ) : (of_nat a ≥ 0) :=
of_nat_le_of_nat_of_le !nat.zero_le
protected theorem le_refl (a : ) : a ≤ a :=
by rewrite [rat.le_def, sub_self]; apply nonneg_zero
protected theorem le_trans (H1 : a ≤ b) (H2 : b ≤ c) : a ≤ c :=
assert H3 : nonneg (c - b + (b - a)), from nonneg_add H2 H1,
begin
revert H3,
rewrite [rat.sub.def, add.assoc, sub_eq_add_neg, neg_add_cancel_left],
intro H3, apply H3
end
protected theorem le_antisymm (H1 : a ≤ b) (H2 : b ≤ a) : a = b :=
have H3 : nonneg (-(a - b)), from !neg_sub⁻¹ ▸ H1,
have H4 : a - b = 0, from nonneg_antisymm H2 H3,
eq_of_sub_eq_zero H4
protected theorem le_total (a b : ) : a ≤ b b ≤ a :=
or.elim (nonneg_total (b - a))
(assume H, or.inl H)
(assume H, or.inr begin rewrite neg_sub at H, exact H end)
protected theorem le_by_cases {P : Prop} (a b : ) (H : a ≤ b → P) (H2 : b ≤ a → P) : P :=
or.elim (!rat.le_total) H H2
protected theorem lt_iff_le_and_ne (a b : ) : a < b ↔ a ≤ b ∧ a ≠ b :=
iff.intro
(assume H : a < b,
have b - a ≠ 0, from ne_zero_of_pos H,
have a ≠ b, from ne.symm (assume H', this (H' ▸ !sub_self)),
and.intro (nonneg_of_pos H) this)
(assume H : a ≤ b ∧ a ≠ b,
obtain aleb aneb, from H,
have b - a ≠ 0, from (assume H', aneb (eq_of_sub_eq_zero H')⁻¹),
pos_of_nonneg_of_ne_zero aleb this)
protected theorem le_iff_lt_or_eq (a b : ) : a ≤ b ↔ a < b a = b :=
iff.intro
(assume h : a ≤ b,
decidable.by_cases
(suppose a = b, or.inr this)
(suppose a ≠ b, or.inl (iff.mpr !rat.lt_iff_le_and_ne (and.intro h this))))
(suppose a < b a = b,
or.elim this
(suppose a < b, and.left (iff.mp !rat.lt_iff_le_and_ne this))
(suppose a = b, this ▸ !rat.le_refl))
private theorem to_nonneg : a ≥ 0 → nonneg a :=
by intros; rewrite -sub_zero; eassumption
protected theorem add_le_add_left (H : a ≤ b) (c : ) : c + a ≤ c + b :=
have c + b - (c + a) = b - a,
by rewrite [sub.def, neg_add, -add.assoc, add.comm c, add_neg_cancel_right],
show nonneg (c + b - (c + a)), from this⁻¹ ▸ H
protected theorem mul_nonneg (H1 : a ≥ (0 : )) (H2 : b ≥ (0 : )) : a * b ≥ (0 : ) :=
assert nonneg (a * b), from nonneg_mul (to_nonneg H1) (to_nonneg H2),
begin rewrite -sub_zero at this, exact this end
private theorem to_pos : a > 0 → pos a :=
by intros; rewrite -sub_zero; eassumption
protected theorem mul_pos (H1 : a > (0 : )) (H2 : b > (0 : )) : a * b > (0 : ) :=
assert pos (a * b), from pos_mul (to_pos H1) (to_pos H2),
begin rewrite -sub_zero at this, exact this end
definition decidable_lt [instance] : decidable_rel rat.lt :=
take a b, decidable_pos (b - a)
protected theorem le_of_lt (H : a < b) : a ≤ b := iff.mpr !rat.le_iff_lt_or_eq (or.inl H)
protected theorem lt_irrefl (a : ) : ¬ a < a :=
take Ha,
let Hand := (iff.mp !rat.lt_iff_le_and_ne) Ha in
(and.right Hand) rfl
protected theorem not_le_of_gt (H : a < b) : ¬ b ≤ a :=
assume Hba,
let Heq := rat.le_antisymm (rat.le_of_lt H) Hba in
!rat.lt_irrefl (Heq ▸ H)
protected theorem lt_of_lt_of_le (Hab : a < b) (Hbc : b ≤ c) : a < c :=
let Hab' := rat.le_of_lt Hab in
let Hac := rat.le_trans Hab' Hbc in
(iff.mpr !rat.lt_iff_le_and_ne) (and.intro Hac
(assume Heq, rat.not_le_of_gt (Heq ▸ Hab) Hbc))
protected theorem lt_of_le_of_lt (Hab : a ≤ b) (Hbc : b < c) : a < c :=
let Hbc' := rat.le_of_lt Hbc in
let Hac := rat.le_trans Hab Hbc' in
(iff.mpr !rat.lt_iff_le_and_ne) (and.intro Hac
(assume Heq, rat.not_le_of_gt (Heq⁻¹ ▸ Hbc) Hab))
protected theorem zero_lt_one : (0 : ) < 1 := trivial
protected theorem add_lt_add_left (H : a < b) (c : ) : c + a < c + b :=
let H' := rat.le_of_lt H in
(iff.mpr (rat.lt_iff_le_and_ne _ _)) (and.intro (rat.add_le_add_left H' _)
(take Heq, let Heq' := add_left_cancel Heq in
!rat.lt_irrefl (Heq' ▸ H)))
protected definition discrete_linear_ordered_field [reducible] [trans_instance] :
discrete_linear_ordered_field rat :=
⦃discrete_linear_ordered_field,
rat.discrete_field,
le_refl := rat.le_refl,
le_trans := @rat.le_trans,
le_antisymm := @rat.le_antisymm,
le_total := @rat.le_total,
le_of_lt := @rat.le_of_lt,
lt_irrefl := rat.lt_irrefl,
lt_of_lt_of_le := @rat.lt_of_lt_of_le,
lt_of_le_of_lt := @rat.lt_of_le_of_lt,
le_iff_lt_or_eq := @rat.le_iff_lt_or_eq,
add_le_add_left := @rat.add_le_add_left,
mul_nonneg := @rat.mul_nonneg,
mul_pos := @rat.mul_pos,
decidable_lt := @decidable_lt,
zero_lt_one := rat.zero_lt_one,
add_lt_add_left := @rat.add_lt_add_left⦄
theorem of_nat_abs (a : ) : abs (of_int a) = of_nat (int.nat_abs a) :=
assert ∀ n : , of_int (int.neg_succ_of_nat n) = - of_nat (nat.succ n), from λ n, rfl,
int.induction_on a
(take b, abs_of_nonneg !of_nat_nonneg)
(take b, by rewrite [this, abs_neg, abs_of_nonneg !of_nat_nonneg])
theorem eq_zero_of_nonneg_of_forall_lt {x : } (xnonneg : x ≥ 0) (H : ∀ ε, ε > 0 → x < ε) :
x = 0 :=
decidable.by_contradiction
(suppose x ≠ 0,
have x > 0, from lt_of_le_of_ne xnonneg (ne.symm this),
have x < x, from H x this,
show false, from !lt.irrefl this)
theorem eq_zero_of_nonneg_of_forall_le {x : } (xnonneg : x ≥ 0) (H : ∀ ε, ε > 0 → x ≤ ε) :
x = 0 :=
have H' : ∀ ε, ε > 0 → x < ε, from
take ε, suppose h₁ : ε > 0,
have ε / 2 > 0, from div_pos_of_pos_of_pos h₁ two_pos,
have x ≤ ε / 2, from H _ this,
show x < ε, from lt_of_le_of_lt this (div_two_lt_of_pos h₁),
eq_zero_of_nonneg_of_forall_lt xnonneg H'
theorem eq_zero_of_forall_abs_le {x : } (H : ∀ ε, ε > 0 → abs x ≤ ε) :
x = 0 :=
decidable.by_contradiction
(suppose x ≠ 0,
have abs x = 0, from eq_zero_of_nonneg_of_forall_le !abs_nonneg H,
show false, from `x ≠ 0` (eq_zero_of_abs_eq_zero this))
theorem eq_of_forall_abs_sub_le {x y : } (H : ∀ ε, ε > 0 → abs (x - y) ≤ ε) :
x = y :=
have x - y = 0, from eq_zero_of_forall_abs_le H,
eq_of_sub_eq_zero this
section
open int
theorem num_nonneg_of_nonneg {q : } (H : q ≥ 0) : num q ≥ 0 :=
have of_int (num q) ≥ of_int 0,
begin
rewrite [-mul_denom],
apply rat.mul_nonneg H,
rewrite [-of_int_zero, of_int_le_of_int_iff],
exact int.le_of_lt !denom_pos
end,
show num q ≥ 0, from le_of_of_int_le_of_int this
theorem num_pos_of_pos {q : } (H : q > 0) : num q > 0 :=
have of_int (num q) > of_int 0,
begin
rewrite [-mul_denom],
apply rat.mul_pos H,
rewrite [-of_int_zero, of_int_lt_of_int_iff],
exact !denom_pos
end,
show num q > 0, from lt_of_of_int_lt_of_int this
theorem num_neg_of_neg {q : } (H : q < 0) : num q < 0 :=
have of_int (num q) < of_int 0,
begin
rewrite [-mul_denom],
apply mul_neg_of_neg_of_pos H,
change of_int (denom q) > of_int 0,
xrewrite [of_int_lt_of_int_iff],
exact !denom_pos
end,
show num q < 0, from lt_of_of_int_lt_of_int this
theorem num_nonpos_of_nonpos {q : } (H : q ≤ 0) : num q ≤ 0 :=
have of_int (num q) ≤ of_int 0,
begin
rewrite [-mul_denom],
apply mul_nonpos_of_nonpos_of_nonneg H,
change of_int (denom q) ≥ of_int 0,
xrewrite [of_int_le_of_int_iff],
exact int.le_of_lt !denom_pos
end,
show num q ≤ 0, from le_of_of_int_le_of_int this
end
definition ubound : := λ a : , nat.succ (int.nat_abs (num a))
theorem ubound_ge (a : ) : of_nat (ubound a) ≥ a :=
have h : abs a * abs (of_int (denom a)) = abs (of_int (num a)), from
!abs_mul ▸ !mul_denom ▸ rfl,
assert of_int (denom a) > 0, from of_int_lt_of_int_of_lt !denom_pos,
have 1 ≤ abs (of_int (denom a)), begin
rewrite (abs_of_pos this),
apply of_int_le_of_int_of_le,
apply denom_pos
end,
have abs a ≤ abs (of_int (num a)), from
le_of_mul_le_of_ge_one (h ▸ !le.refl) !abs_nonneg this,
calc
a ≤ abs a : le_abs_self
... ≤ abs (of_int (num a)) : this
... ≤ abs (of_int (num a)) + 1 : le_add_of_nonneg_right trivial
... = of_nat (int.nat_abs (num a)) + 1 : of_nat_abs
... = of_nat (nat.succ (int.nat_abs (num a))) : of_nat_add
theorem ubound_pos (a : ) : ubound a > 0 :=
!nat.succ_pos
open nat
theorem binary_nat_bound (a : ) : of_nat a ≤ 2^a :=
nat.induction_on a (zero_le_one)
(take n : nat, assume Hn,
calc
of_nat (nat.succ n) = (of_nat n) + 1 : of_nat_add
... ≤ 2^n + 1 : add_le_add_right Hn
... ≤ 2^n + (2:rat)^n : add_le_add_left (pow_ge_one_of_ge_one two_ge_one _)
... = 2^(succ n) : pow_two_add)
theorem binary_bound (a : ) : ∃ n : , a ≤ 2^n :=
exists.intro (ubound a) (calc
a ≤ of_nat (ubound a) : ubound_ge
... ≤ 2^(ubound a) : binary_nat_bound)
end rat